5P Differential expression patterns of immune checkpoint markers in tumour-stromal microenvironment of primary and chemoreduced retinoblastoma. (15th December 2019) - Singh, L; Singh, M K; Rizvi, M A; Pushker, N; Sen, S; Kashyap, S
Abstract: Background: The goal of this study is to identify the pathological findings and expression of immune checkpoint marker (PD-1, PD-L1, and CTLA-4) in the tumor microenvironment of both primary and chemoreduced retinoblastoma and correlate with clinicopathological parameters and patient outcome. Methods: Total of 262 prospective cases was included prospectively in which 144 cases underwent primary enucleation and 118 cases received chemotherapy/radiotherapy before enucleation (chemoreduced retinoblastoma). Immunohistochemistry, qRT-PCR and western blotting were performed to evaluate the expression pattern of immune checkpoint markers in primary and chemoreduced retinoblastoma. Results: Tumor microenvironment was different for both primary and chemoreduced retinoblastoma. Expression of PD-1 was found in 29/144 (20.13%) and 48/118 (40.67%) in primary and chemoreduced retinoblastoma respectively, whereas PD-L1 was expressed in 46/144 (31.94%) and 22/118 (18.64%) in cases of primary and chemoreduced retinoblastoma respectively. Expression pattern of CTLA-4 protein was similar in both groups of retinoblastoma. On multivariate analysis, massive choroidal invasion, bilaterality and PD-L1 expression (p = 0.034) were found to be statistically significant factors in primary retinoblastoma whereas PD-1 expression (p = 0.015) and foamy macrophages were significant factors in chemoreduced retinoblastoma. Overall survival reduced in cases of PD-L1 (80.76%) expressed primary retinoblastoma, and PD-1 (63.28%) expressed chemoreduced retinoblastoma. Conclusion: This is the first of its kind study predicting a relevant role of the immune checkpoint markers in primary and chemoreduced retinoblastoma with prognostic significance. Differential expression of these markers in both group of retinoblastoma is a novel finding and might be an interesting and beneficial target for chemoresistant tumors. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.